2018
DOI: 10.1177/1077559518808221
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Controlled Trial on the Effectiveness of Family Group Conferencing in Child Welfare: Effectiveness, Moderators, and Level of FGC Completion

Abstract: The present study examined the effectiveness of Family Group Conferencing (FGC) in child welfare. Effects were operationalized in terms of child safety (child maltreatment, supervision order, and out-of-home placement), number of professional services used, parental empowerment, and social support in a 1-, 3-, 6-, and 12-month follow-up. Furthermore, the influence of family characteristics and the level of FGC completion were examined. A total of 328 families were included, randomly assigned to an experimental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 32 publications
2
12
0
1
Order By: Relevance
“…It seems that families that were offered FGC but refused did benefit more from the FGC approach, compared to CAU, than families who dropped out in the preparation phase or completed all phases. This finding seems in line with the results in an earlier study, in which was found that lower program fidelity (resulting from drop out between the referral and conference phase), was related to higher scores on empowerment [ 10 ]. Apparently, when families decided to refuse FGC and to make a care plan with the child welfare worker, this decision resulted in larger effects and sometimes lower costs compared to CAU than when families completed all phases of FGC.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…It seems that families that were offered FGC but refused did benefit more from the FGC approach, compared to CAU, than families who dropped out in the preparation phase or completed all phases. This finding seems in line with the results in an earlier study, in which was found that lower program fidelity (resulting from drop out between the referral and conference phase), was related to higher scores on empowerment [ 10 ]. Apparently, when families decided to refuse FGC and to make a care plan with the child welfare worker, this decision resulted in larger effects and sometimes lower costs compared to CAU than when families completed all phases of FGC.…”
Section: Discussionsupporting
confidence: 91%
“…With respect to the first aim of the study, we found that six as well as 12 months after a care plan was made, FGC was equally effective as CAU in reducing child maltreatment, which is in line with previous research [ 7 , 8 , 10 ]. Our findings at six and 12 months suggest that effects of FGC in terms of child safety are stable over time.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations